Преобразуйте в многочлен выражение:

1) -x(x+2)-(x-7)(x^2+7x+49)

2) (b-2)b-(b-1)(b+1)

3) -(с+5)^2-(c-4)(c+3)

4) 2(b+2)(b+3)-(b-1)^3

Хоть что нибудь помогите решить. Спасибо большое заранее.

1

Ответы и объяснения

  • MRSG
  • отличник
2013-04-05T18:40:30+04:00

1)  -x(x+2)-(x-7)(x^2+7x+49)=- х² - 2х - х³ + 7³

2)  (b-2)b-(b-1)(b+1)=b² - 2b - b²+1=1-2b

3) -(с+5)^2-(c-4)(c+3)=-c²-10c-25-c²-3c+4c+12=-2c²-9c+12

4) 2(b+2)(b+3)-(b-1)^3=(2b+4)(b+3)-(b-1)^3=2b²+3b+4b+12-(b-1)(b²-2b+1)=2b²+3b+4b+12-(b³-2b²+b-b²+2b-1)=2b²+3b+4b+12-b³+2b²-b+b²-2b+1=5b²-b³+13+4b